Improving palliative care for cancer : summary and recommendations - Foley, Kathleen M., 1944-; Gelband, Hellen (Compass series (Washington, D.C.), 2001)
It is innately human to comfort and provide care to those suffering from cancer, particularly those close to death. Yet what seems self-evident at an individual, personal level has, by and large, not guided policy at the level of institutions in this country. There is no argument that palliative care should be integrated into cancer care from diagnosis to death. But significant barriers-attitudinal, behavioral, economic, educational, and legal-still limit access to care for a large proportion of those dying from cancer, and in spite of tremendous scientific opportunities for medical progress against all the major symptoms associated with cancer and cancer death, public research institutions have not responded. In accepting a single-minded focus on research toward cure, we have inadvertently devalued the critical need to care for and support patients with advanced disease, and their families. This report builds on and takes forward an agenda set out by the 1997 IOM report Approaching Death: Improving Care at the End of Life, which came at a time when leaders in palliative care and related fields had already begun to air issues surrounding care of the dying. That report identified significant gaps in knowledge about care at the end of life and the need for serious attention from biomedical, social science, and health services researchers. Most importantly, it recognized that the impediments to good care could be identified and potentially remedied. The report itself catalyzed further public involvement in specific initiatives-mostly pilot and demonstration projects and programs funded by the nonprofit foundation community, which are now coming to fruition.